Sensing H+ with conventional neural probes - Trantidou,T; Prodromakis,T; Tsiligkiridis,V; Chang,YC; Toumazou,C (Applied Physics Letters, 2013)
In this paper, we demonstrate a technique for transforming commercially available neural probes used for electrical recordings, into chemical sensing devices for detection of ionic concentrations in electrolytes, with particular emphasis to pH. This transformation requires a single post-processing step to incorporate a thin indium tin oxide membrane for sensing H+. Measured results indicate a chemical sensitivity of 28 mV/pH, and relatively low leakage currents (2–10 nA) and drifts (1–10 mV/h). The proposed sensing device demonstrates the possibility of a low-cost implementation that can be reusable and thus versatile, with potential applications in real-time extracellular but mainly intracellular chemical monitoring.